Comparing stress, areas of stress and coping-strategies between distance-learning and on-campus students – A mixed-methods approach - Drüge, Marie; Fritsche, Lara; Bögemann, Cornelia; Apolinário-Hagen, Jennifer; Salewski, Christel (Frontiers in Psychology, 2022)
In recent years, the increase in stress experienced by students, and the related health problems have become a key challenge for health psychologists. The aim of this cross sectional survey study was to compare stress, areas of stress and coping-strategies of 246 distance-learning (81.7% female; 33.62 years, SD=9.30) and 254 on-campus students (82.3% female; 24.23 years, SD=3.99). One-way analyses of variance showed no significant differences in perceived stress and stress symptoms between the student groups. Stress-inducing areas were revealed by qualitative content analysis. Chi-square tests showed that on-campus students significantly more often reported study- and performance-related areas, whereas conflicts between work and private life were more present among distance-learning students. Results also indicated that on-campus students significantly more often cope with stress by means of social support. These findings may help tailoring stress-management interventions for different student groups.